2016
DOI: 10.1172/jci84014
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase KDM2B regulates lineage commitment in normal and malignant hematopoiesis

Abstract: Graph shows the mean ± SEM. n = 3. *P < 0.05. (G) Immunofluorescent staining of aortas from E10.5 embryos for KDM2B (red; nuclear) and c-Kit (green; cell surface). White arrow shows budding hemogenic endothelium and yellow arrow a circulating "stem-like" cell. Nuclei were stained with DAPI (blue). Scale bars: 10 μm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 65 publications
(92 reference statements)
2
102
0
Order By: Relevance
“…Many PcG null mutations of one of the orthologs in mice can survive to later embryonic stages; some of them are even viable, showing very mild phenotypes [94] (see Tables 2-5). Furthermore, analyzing the mouse phenotypes of late lethal PcG mutations, it became obvious that although these factors play profound role in homeotic regulation [158,159], their epigenetic repressor functions are also important in hematopoiesis [160][161][162][163] (reviewed in [164] and [165]), neuronal [154,166] (reviewed in [167]) cardiac [168][169][170] and skeletal muscle differentiation [171], as well as in the maintenance of germ cell fate [172][173][174][175].…”
Section: Mammalian Pcg Gene Functions: Parallels and Differences Betwmentioning
confidence: 99%
See 1 more Smart Citation
“…Many PcG null mutations of one of the orthologs in mice can survive to later embryonic stages; some of them are even viable, showing very mild phenotypes [94] (see Tables 2-5). Furthermore, analyzing the mouse phenotypes of late lethal PcG mutations, it became obvious that although these factors play profound role in homeotic regulation [158,159], their epigenetic repressor functions are also important in hematopoiesis [160][161][162][163] (reviewed in [164] and [165]), neuronal [154,166] (reviewed in [167]) cardiac [168][169][170] and skeletal muscle differentiation [171], as well as in the maintenance of germ cell fate [172][173][174][175].…”
Section: Mammalian Pcg Gene Functions: Parallels and Differences Betwmentioning
confidence: 99%
“…Ablation of KDM2B in ES cells causes DNA hypermethylation [285]. One of the latest studies found that Kdm2b is required for hematopoietic cell development and, during this process, KDM2B regulates cell lineage commitment in cooperation with PcG and TrxG complexes [162]. S-Phase Kinase Associated Protein 1a (SKP1) was first identified in a complex with human CyclinA-Cyclin-Dependent Kinase 2 (CDK2) in conjunction with SKP2 [286] and later SKP1 was found promoting ubiquitination and degradation of various cell cycle regulators [287,288].…”
Section: Detailed Description Of the Composition And Function Of Diffmentioning
confidence: 99%
“…PRC1 complexes display a great plasticity in eukaryotes with at least six biochemically distinct groups (15). All these complexes operate in collaboration with the E3 ubiquitin ligases Ring1a or Ring1b, which catalyse the mono-ubiquitination of H2A (H2Aubq) on lysine 119 (H2AK119 (23,24). The finding that PRC1 has the ability to establish different repressive transcriptional programs raises questions about the mechanisms used by cells to specifically recruit the complexes to the chromatin.…”
Section: Perspectivementioning
confidence: 99%
“…More recently, the JmjC domain histone H3K36 di-demethylase KDM2B/FBXL10 has been also shown to play an important role in definitive hematopoiesis (17). Kdm2b is highly expressed in the HE, and its deletion ( Tie2 Cre ) caused embryonic lethality due to a precipitous drop in the number of hemogenic endothelial cells within the AGM.…”
Section: Introductionmentioning
confidence: 99%
“…Kdm2b is highly expressed in the HE, and its deletion ( Tie2 Cre ) caused embryonic lethality due to a precipitous drop in the number of hemogenic endothelial cells within the AGM. On the other hand, Vav1 Cre ;Kdm2b fl/fl mice were viable, but displayed a dramatic reduction in the number of long-term HSCs as well as defective lymphopoiesis which was accompanied by a concomitant upregulation of myeloid differentiation (17). A similar phenotype was also observed in Mx1 Cre ;Kdm2b fl/fl mice upon pIpC administration suggesting an important role for Kdm2b in the maintenance of HSPCs and regulation of lymphopoiesis, the latter in a JmjC domain dependent manner (17).…”
Section: Introductionmentioning
confidence: 99%